Volume 1: Advances in Aerospace Technology; Energy Water Nexus; Globalization of Engineering; Posters 2011
DOI: 10.1115/imece2011-65255
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Influence of Endwall Fences Located in the Vicinity of the Leading Edge-Endwall Junction of Nozzle Guide Vanes

Abstract: Secondary flow characteristics like horseshoe vortices and related total pressure losses decrease turbine efficiency. Computerized simulations of potentially favorable modifications in turbine systems could provide a fast, numerical and inexpensive method of evaluating their effects on flow properties: This paper consists of a comparative numerical study of the flow characteristics of a domain containing a vertical cylinder subjected to cross flow and upstream endwall modifications. Analyzing the flow around a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The static pressure coefficient calculated over a line on the cylinder surface, according to Equation 4, is an example to such a parameter. A grid independence study conducted in this fashion was realized in our previous publications [19], [20] which led to the current paper: The grid independence study indicated that the flow modeling technique used in our studies (the meshing done in Gambit and the flow solution conducted in Fluent) accurately captured the static pressure coefficient, and generated identical results with three different mesh sizes [19], [20] . Hence, a mesh size which will be on the same order of magnitude for all cases was selected for use.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…The static pressure coefficient calculated over a line on the cylinder surface, according to Equation 4, is an example to such a parameter. A grid independence study conducted in this fashion was realized in our previous publications [19], [20] which led to the current paper: The grid independence study indicated that the flow modeling technique used in our studies (the meshing done in Gambit and the flow solution conducted in Fluent) accurately captured the static pressure coefficient, and generated identical results with three different mesh sizes [19], [20] . Hence, a mesh size which will be on the same order of magnitude for all cases was selected for use.…”
Section: Methodsmentioning
confidence: 94%
“…Please refer to Gokce [19] and Gokce and Camci [20] for further methodology details, verification methods and geometrical information which are not presented here for the sake of brevity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations